THE EFFECT OF SCIENTIFIC APPROACH COMBINES LEARNING GUIDED DISCOVERY TO CURIOSITY OF STUDENTS - Prasetyo, Teguh; Fitri, Ananda Marliana (DIDAKTIKA TAUHIDI: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research article is the result of a scientific approach that combines guided discovery models to describe the increase of curiosity and student learning outcomes in science subjects. The research approach uses quantitative research with Nonequivalent control group design. The subjects of the study were fifth grade of 76 students of SDN Cibedug, Bogor 2016/2017. The data collection instruments used consisted of observation techniques, scale questionnaires, and test of learning outcomes. The result data showed curiosity and learning result of significance value less than 0.05. Analysis of learning result data obtained t-count value of 3.389 and t-critical at 5% significance level is 0.1992. Thus, t-count> t-table (3.389> 0.1992) which means there is an influence from the scientific approach combining the guided discovery model to the learning outcomes. The average posttest increase of experimental class curiosity was 52.00 while control class was 46.2. The research conclusion of a scientific approach combining the guided discovery model in the field of IPA lesson studies has an influence on learning outcomes and improves the curiosity of elementary school students.